PENEGAKAN HUKUM TERHADAP PENADAHAN BARANG HASIL CURIAN DI POLRES ROKAN HILIR BERDASARKAN KITAB UNDANG-UNDANG HUKUM PIDANA - Siregar, Anta Arief; Kadaryanto, Bagio; Harahap, Irawan (The Juris, 2024)
Items such as electronics, motor vehicles, and other valuable goods are sold quickly, making stolen goods difficult to trace. This criminal network complicates law enforcement efforts. Law enforcement against theft and fencing must be carried out firmly to maintain order and a sense of security in society. Perpetrators of theft and fencing can both be subjected to criminal sanctions in accordance with the provisions of the Indonesian Penal Code (KUHP). The purpose of this study is to analyze law enforcement against fencing stolen goods in Rokan Hilir Police jurisdiction based on the Penal Code. The method used is sociological legal research. The results of the study reveal that law enforcement against fencing stolen goods in the Rokan Hilir Police jurisdiction, based on the Penal Code, has not been effectively implemented. This is evidenced by the increasing prevalence of fencing stolen goods, as referred to in Article 480 of the Penal Code. This article regulates the criminal act of fencing, where a person can be punished if they are proven to have knowingly received, purchased, or stored goods resulting from a criminal act such as theft. The obstacles in law enforcement against fencing stolen goods in the Rokan Hilir Police jurisdiction, based on the Penal Code, include the difficulty of proving the element of intent on the part of the fencing perpetrators, the low public awareness of reporting fencing activities or involvement in the trade of stolen goods, challenges in identifying fencing perpetrators, and limited resources and technology for tracking stolen goods transactions, which further hinder the law enforcement process. Efforts to overcome these obstacles include improving coordination among law enforcement agencies, strengthening the capacity of investigative personnel in understanding and applying the articles governing the crime of fencing, and adopting a more inclusive approach with the community.